2017
DOI: 10.1063/1.4974548
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site delamination detection and quantification in composites through guided wave based global-local sensing

Abstract: Abstract. This paper presents a guided wave based global-local sensing method for rapid detection and quantification of multi-site delamination damage in large composite panels. The global-local approach uses a hybrid system consisting of a piezoelectric transducer (PZT) for generating guided waves and a non-contact scanning laser Doppler vibrometer (SLDV) for acquiring guided wave data. The global-local method is performed in two steps. First, a phased array configured of a small number of SLDV scan points (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Authors of [13] conducted four delamination-type defects detection, simulated by thin Teflon film inserts embedded between selected layers of the specimen. Another detection process of such defects was done in [14] and [15] (scientists in [15] considered multi-layered delamination). However, all of these works [13], [14], [15] are related to elastic waves generation by piezoelectric transducer (PZT) instead of ACT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Authors of [13] conducted four delamination-type defects detection, simulated by thin Teflon film inserts embedded between selected layers of the specimen. Another detection process of such defects was done in [14] and [15] (scientists in [15] considered multi-layered delamination). However, all of these works [13], [14], [15] are related to elastic waves generation by piezoelectric transducer (PZT) instead of ACT.…”
Section: Introductionmentioning
confidence: 99%
“…Another detection process of such defects was done in [14] and [15] (scientists in [15] considered multi-layered delamination). However, all of these works [13], [14], [15] are related to elastic waves generation by piezoelectric transducer (PZT) instead of ACT. In turn, in [16] delamination defects detection using ACT to generate acoustic waves and scanning laser Doppler vibrometer (SLDV) to detect elastic waves was performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…impact events with nearly invisible marks on their surface, known as barely visible impact damage (BVID) [4]. Normally, BVID from bird strikes, hailstorms and tool drops is characterised by delamination, matrix micro-cracking and fibre failure [5]. These material flaws tend to evolve with high rates under operating dynamic stresses and, thus, safety regulations in aviation require frequent inspections of composite structures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Guided wave damage detection and quantification techniques reported in the literature range from sparse data methods via sensor arrays to dense data methods utilizing full wavefield imaging through laser Doppler vibrometry. Numerous authors have reported on experimental guided wave techniques and simulation-aided investigation of guided wave methods [12] [13] [14] [15] [16] [17] [18]. For both bulk and guided wave based ultrasound methods, realistic ultrasound simulation tools can significantly aid the development and optimization of inspection techniques and can assist in the interpretation of experimental data.…”
Section: Introductionmentioning
confidence: 99%